A far-red emitting probe for unambiguous detection of mobile zinc in acidic vesicles and deep tissue1. Issue 3 (16th March 2015) - Rivera-Fuentes, Pablo; Wrobel, Alexandra T.; Zastrow, Melissa L.; Khan, Mustafa; Georgiou, John; Luyben, Thomas T.; Roder, John C.; Okamoto, Kenichi; Lippard, Stephen J.
<x xml:space="preserve">Abstract</x> A fluorescent sensor that is pH-insensitive and compatible with two-photon microscopy was developed and applied to live cell and deep tissue imaging.